Uji Daya Hasil, Komponen Hasil, dan Morfofisiologi Beberapa Genotipe Padi Beras Merah dengan Sistem Gogo - Irmayani, Irmayani; Kisman, Kisman; Aryana, I Gusti Putu Muliartha (LPPM Universitas Mataram, 2025)
This study aimed to determine the yield potential, yield components, and morphophysiology of several red rice genotypes under upland (gogo) cultivation system. The research was conducted from August to December 2024 in Wanasaba Village, East Lombok, West Nusa Tenggara. A Randomized Completely Block Design (RCBD) was used with 12 genotypes as treatments, consisting of five lines: 19I-06-09-23-03 (G1), 21B-57-21-21-23 (G2), 23F-04-10-18-18 (G3), 23A-56-20-07-20 (G4), 23A-56-22-20-05 (G5), and 7 varieties: PBM UBB1 (G6), Danau Gaung (G7), Inpago 8 (G8), Inpago 12 (G9), Rindang (G10), Inpago Unram I (G11), and Beak Ganggas (G12), each replicated three times. The observed parameters including: relative leaf water content, chlorophyll content, number of days to flowering, number of days to harvesting, plant height, flag leaf length, total tiller number, productive tiller number, non-productive tiller number, panicle length, number of filled grains per panicle, number of unfilled grains per panicle, 1000-grain weight, weight of filled grains per clump, and yield per hectare. The data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level. If significant differences were found, Duncan’s Multiple Range Test (DMRT) at the 5% level was conducted. The results of this study showed that red rice grown under upland conditions exhibited diverse yield potentials, yield components, and morphophysiological characteristics, except for traits such as number of days to flowering, leaf chlorophyll content, relative leaf water content, number of non-productive tillers, and number of empty grains per panicle. The highest yields were obtained on genotypes G4 (line 23A-56-20-07-20), G12 (Beak Ganggas), and G10 (Rindang), with yields of 5,81, 5,78, and 5,61 ton/ha respectively. Genotypes G4 and R have early harvest age, relatively moderate plant height, moderate number of productive tillers, moderate panicles, large number of filled grains with high weight of filled grains, namely G4 (36,30 grams) and R (35,10 grams). While BG (Beak Ganggas) has long panicles, large number of filled grains with high weight of filled grains, namely G4 (3605 grams), although the number of productive tillers is small.